NICAF Yokohama '93 : The 2nd International Contemporary Art Fair, Japan. (Tokyo : NICAF Executive Committee, 1993)
Nakamura, Masato ; Ueki, Kenji ; Kawaguchi, Tatsuo ; Shoda, Tsuneaki ; Inayoshi, Minoru ; Lichtenstein, Roy ; Warhol, Andy ; Shirakawa, Yoshio ; Nakahara, Nobuhiro ; etc.
NICAF Yokohama '93 : The 2nd International Contemporary Art Fair, Japan, 1993.3.9. -1993.3.23, Pacifico Yokohama
Japans & Engels
kunstcatalogus